2022
DOI: 10.30574/wjarr.2022.15.3.0924
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ABO blood group in surgical patients at a tertiary hospital in rivers state, Nigeria

Abstract: The significance of determining the distribution of blood group of patients prior to surgical procedures cannot be over-emphasized. This is because surgical patients may need blood transfusion pre-operatively, intra-operatively or post-operatively. The distribution of ABO blood group varies in different regions of the world. Aim: To determine the distribution of ABO blood group in surgical patients at the Rivers State University Teaching Hospital (RSUTH). Method: This was a one-year retrospective study of Surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…These findings were similar to the findings by Mohamud et al in Somalia. [1,2] The most common surgeries were among the obstetrics and gynaecology subjects and this may be one of the reasons why the commonest blood group from this study was found in the female subjects (37.9%) (see tables 1,5 and 6).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…These findings were similar to the findings by Mohamud et al in Somalia. [1,2] The most common surgeries were among the obstetrics and gynaecology subjects and this may be one of the reasons why the commonest blood group from this study was found in the female subjects (37.9%) (see tables 1,5 and 6).…”
Section: Discussionmentioning
confidence: 67%
“…The Rhesus (Rh) antigen is found on the surface of human red blood cell (RBC) membrane. [1] The ABO system remain the most clinically significant blood group antigens on the red cell membrane. [1,2] This is important in obstetric practice including those involved in surgeries due to the fact that if the mother is RhD-negative and the fetus RhD-positive, she has potential capacity to form antibodies if exposed to fetal antigens, a process known as Rh-D sensitization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations